2020
DOI: 10.1061/(asce)cp.1943-5487.0000931
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mobile Augmented Reality System on Cognitive Behavior and Performance during Rebar Inspection Tasks

Abstract: Mobile augmented reality (MAR) enhances the real world through the superimposition of computer-generated information while not interfering with their users' mobility, having great potential to support various construction tasks. However, such information may lead to cognitive overload and thus could lead to adverse effects on the performance of tasks. Also, the narrowing of a user's field of view that comes with MAR use could limit his/her ability to notice events in their surroundings. Therefore, it is import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…This score is based on the weighted average of ratings on six subscales: mental demand, physical demand, temporal demand, performance, effort, and frustration. NASA TLX has measured CL in physical, virtual, simulations, and lab tests [15,19,54,55].…”
Section: Impact Of Virtual Reality On the Cognitive Load Task Perform...mentioning
confidence: 99%
See 1 more Smart Citation
“…This score is based on the weighted average of ratings on six subscales: mental demand, physical demand, temporal demand, performance, effort, and frustration. NASA TLX has measured CL in physical, virtual, simulations, and lab tests [15,19,54,55].…”
Section: Impact Of Virtual Reality On the Cognitive Load Task Perform...mentioning
confidence: 99%
“…Augmented reality frequently supports users' cognitive abilities by providing superimposed information. However, such knowledge can cause cognitive overload, which might negatively impact the participants' performance [19]. Zhong studied that VR training may help individuals with their cognitive and executive function [20].…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular concern in a construction site where spatial and situational awareness is critical for site safety (S5). In an experiment, Abbas et al (2020) found that rebar-drawing information provided by superimposed computer imagery helped to reduce their users' cognitive load in a 'clean' environment, compared to a paper-based (control) group. The paper-based control group took longer but were able to identify more errors than those using MAR technology due to the perception issues associated with MAR systems.…”
Section: Potential Interventions and Factors Impacting The User Exper...mentioning
confidence: 99%
“…Head-mounted MAR was found to decrease the users understanding of the surrounding environment and increase the inspection task completion times, not only compared to the control group but also compared to a tablet-based MAR test group. Overall, the two main existing modalities of MAR-based inspection were found to negatively affect cognitive load, task performance and situational awareness (Abbas et al 2020). The phenomenon of simulation sickness, a subset of motion sickness, must also be considered when proposing a MAR system for head-mounted MAR devices.…”
Section: Potential Interventions and Factors Impacting The User Exper...mentioning
confidence: 99%
“…Kwon et al (2014) adds an AR app to this defect management framework. Mobile AR systems allow easier inspections of concrete and masonry embedment (Olson et al, 2019) and reinforcement (Abbas et al, 2020). AR inspection tools with 3D annotations have proved to be even more effective (Marino, 2021).…”
Section: Ar In the Construction Industrymentioning
confidence: 99%